PENGARUH GANGGUAN PRIBADI, GANGGUAN EKSTEREN, DAN GANGGUAN ORGANISASI TERHADAP INDEPENDENSI AUDITOR DENGAN KOMITMEN PROFESIONAL SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Inspektorat Provinsi Riau dan Provinsi Sumatera Barat) - Setiawan Harsa; Emrinaldi Nur DP; Hariadi Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of personal interference, external interference, and interference with the independence of the auditor organization on professional commitment as an intervening variable. The location of this research in the Provincial Inspectorate of Riau and West Sumatra Provincial Inspectorate. In this study, the population used is the Riau Provincial Inspectorate and the Inspectorate of West Sumatra Province. Respondents in this study were all pengawai Inspectorate Province of Riau and West Sumatra. Samples of this research were 53 respondents. The data used are primary data. The analytical method used is the analysis of PLS (Partial Least Square). The results showed a direct influence are: 1) Personal Disorders affect the auditor's independence. 2) Disturbance affect the external auditor's independence. 3) Organization Disorders affect the auditor's independence. And the study also showed their influence is indirectly personal Disorders, external interference, and interference organizations have indirect influence on the independence of auditors with professional commitment. Based on the results of R-Square variable auditor independence by 85.3% and variable professional commitment of 66.3%.Keyword : Personal Disorder, External Disorders, Disorders Organisation, Auditor Independence, and Professional Commitment.